Объяснение: 1) ∫₄⁹√xdx =(2/3)·x√x |₄⁹= (2/3)· (9√9 = 4√4)=(2/3)·(27-8)= 2·19/3=38/3
2) 1+ log₂(x+5) = log₂(3x-1) +log₂(x-1) , ОДЗ: х-1>0, x>1 ⇔ log₂2 +log₂(x+5) = log₂(3x-1) +log₂(x-1) ⇔ log₂ (2x+10) = log₂ (3x²-4x+1) ⇒ 2x+10= 3x²-4x+1 ⇒ 3x²-6x-9 =0⇒ x²-2x - 3=0, D= 4+12=16>0, ⇒x₁=(2+4)/2=3, x₂=(2-4)/2=-1 (не удовлетворяет ОДЗ уравнения). ответ: х=3 №3 tgα=y'(x₀), y'(x)=(x³)'=3x² ⇒ т.к. х₀ =0, то tgα=y'(x₀)=3·0²=0
1) х = 0,25
2) х = -5
3) y= -0.6
4) y = -0.75
Объяснение:
1) x(x-4)=2+(x-1)²;
х*х + х*(-4) = 2 + (х-1)(х+1)
- 4х = 2+ х*х + х*1 - 1*х - 1*1
- 4х = 2 +
+ х - х - 1
-4х - х + х = 2 - 1
-4х = 1
х = 1/4
х = 0,25
2). (x+2)(x-3)-3=(x+1)²
х*х + х*(-3) + 2*х + 2*(-3) = (х+1)(х-1)
- 3х + 2х - 6 =
- х + х - 1
-х = 5 (умножить на -1)
х = -5
3)y(5-y)=1-(y+2)²
5у - = 1 - (y+2)(y-2)
5y - = 1 -
- 2y + 2y - 4
5y + 2y -2y = 1-4
5y = -3
y = -3/5
y = -0.6
4) (y-1)²-(y+1)(y-7)=0.
(y-1)(y+1) - + 7y + y + 7 = 0
+ y - y - 1 -
+ 7y + y + 7 = 0
8y = -6
y = -6/8
y = -0.75
2) = ( - 1/3x^7y^3 )
N 2
a) 12a^7 = 3a^2•4a^5
б) 36а^4b^2 = 12a^3b•3ab